Risk factors for kidney damage in COVID-19 patients admitted to the intensive care unit - Diana K. Sarkisian; Natalia V. Chebotareva; Valerie McDonnell; Armen V. Oganesyan; Tatyana N. Krasnova; Egor A. Makarov (Russian Open Medical Journal)
Background — Acute kidney injury (AKI) reaches 29% in the intensive care unit (ICU). Our study aimed to determine the prevalence, features, and the main AKI factors in critically ill patients with coronavirus disease 2019 (COVID-19). Material and Methods — The study included 37 patients with COVID-19. We analyzed the total blood count test results, biochemical profile panel, coagulation tests, and urine samples. We finally estimated the markers of kidney damage and mortality. Result — All patients in ICU had proteinuria, and 80.5% of patients had hematuria. AKI was observed in 45.9% of patients. Independent risk factors were age more than 60 years, increased C-reactive protein (CRP) level, and decreased platelet count. Conclusion — Kidney damage was observed in most critically ill patients with COVID-19. The independent risk factors for AKI in critically ill patients were elderly age, a cytokine response with a high CRP level.